SISTEM PAKAR MENDIAGNOSA PENYAKIT GUMBORO PADA AYAM BROILER DENGAN METODE CERTAINTY FACTOR - Garuda Ginting; Siska Subuh Hati Tarigan; Fadlina Fadlina (JURNAL MEDIA INFORMATIKA BUDIDARMA, 2017)
The rapid development of technology along with the increasingly complex and complex human needs enable the field of computer science including expert systems to be used widely in various fields such as business, health, education and so on. Gumboro disease is caused by IBD virus originating from family (family) Birnaviridae virus and genus Avibirnavirus. This virus has two serotypes I and II. Only serotype I, is pathogenic (causes pain) in chickens. Serotype II attacks Turkey and is not pathogenic in chickens. The certainty factor was introduced by Shortliffe Buchanan in the making of MYCIN (Wesley, 1984). Certainty Factor (CF) is the value of the clinical parameters given by MYCIN to indicate the magnitude of trust.